2017
DOI: 10.37358/mp.17.2.4827
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characteristics of Mini-implants Sterilised by Different Chemical and Physical Procedures

Abstract: One hundred micro-implants from two different manufacturers were used in the study. From each manufacturer (Link from MISTM and Yesanchor from OrlusTM) the implants were divided in 5 groups: G0 (n=10) new, unused, G1 (n=10) mini-implants inserted in pig bone and removed, ultrasonically cleaned, followed by autoclave sterilization, G2 (n=10) same insertion protocol of group 2 followed by chemical cleaning with phosphoric gel and autoclave strerilization, G3 (n=10) same insertion protocol of group 1 followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The most important characteristic in using dental biomaterials are their biocompatibility [25,26]. The results of Pop [27] on properties of epoxy coated NiTi open coil springs indicated that aesthetic coating might affect their stiffness. Researches of Zegan et al [28], focused on the orthodontic mini-implant coated with silver doped hydroxyapatite, observed that nanoparticles deposition on titanium surface of miniimplants offers the possibility design structural and morphological features on nanoscale.…”
Section: Resultsmentioning
confidence: 99%
“…The most important characteristic in using dental biomaterials are their biocompatibility [25,26]. The results of Pop [27] on properties of epoxy coated NiTi open coil springs indicated that aesthetic coating might affect their stiffness. Researches of Zegan et al [28], focused on the orthodontic mini-implant coated with silver doped hydroxyapatite, observed that nanoparticles deposition on titanium surface of miniimplants offers the possibility design structural and morphological features on nanoscale.…”
Section: Resultsmentioning
confidence: 99%